Задача Коші для рівнянь з дробовими похідними за часовою та просторовими змінними у просторах узагальнених функцій - Лопушанська, Г.П.; Лопушанський, А.О. (Український математичний журнал, 2012)
Доказана теорема существования и единственности и получено представление с помощью вектор-функции Грина решения задачи Коши
с производной Римана – Лиувилля u(β)t порядка β∈(0,1) и u0, F из пространств обобщенных функций. Установлен характер особенностей решения при t=0 в зависимости от порядка сингулярности заданной обобщенной функции в начальном условии и характера степенных особенностей функции в правой части уравнения. Здесь определено с помощью преобразования Фурье. We prove the theorem on existence and uniqueness of solution to the Cauchy problem
where u(β)t is the Riemann–Liouville fractional derivative of order β ∈ (0, 1) and u 0 and F belong to spaces of generalized functions. A representation of this solution is obtained by using the vector Green function. We also establish the character of singularities of the solution for t = 0 depending on the order of singularity of a given generalized function in the initial condition and the character of power singularities of the function on the right-hand side of the equation. In this case, the fractional n-dimensional Laplace operator is defined by using the Fourier transformation